Asexual genome evolution in the apomictic Ranunculus auricomus complex: examining the effects of hybridization and mutation accumulation. Issue 23 (6th November 2013) - Pellino, Marco; Hojsgaard, Diego; Schmutzer, Thomas; Scholz, Uwe; Hörandl, Elvira; Vogel, Heiko; Sharbel, Timothy F.
Abstract Asexual lineages are thought to be prone to extinction because of deleterious mutation accumulation (Muller's ratchet). Here, we analyse genomic effects of hybridity, polyploidy and allelic divergence in apomictic plants, and identify loci under divergent selection among sexual/apomictic lineages. RNAseq was used to sequence the flower‐specific transcriptomes of five genotypes of the Ranunculus auricomus complex, representing three sexual and two apomictic reproductive biotypes. The five sequence libraries were pooled and de novo assembly performed, and the resultant assembly was used as a backbone for a subsequent alignment of each separate library. High‐quality single‐nucleotide (SNP) and insertion–deletion (indel) polymorphisms were mined from each library. Annotated genes for which open reading frames (ORF) could be determined were analysed for signatures of divergent versus stabilizing selection. A comparison between all genotypes supports the hypothesis of Pleistocene hybrid origin of both apomictic genotypes from R. carpaticola and R. cassubicifolius, with subsequent allelic divergence of apomictic lineages (Meselson effect). Pairwise comparisons of nonsynonymous (dN) to synonymous (dS) substitution rate ratios between apomictic and sexual genotypes for 1231 genes demonstrated similar distributions for all comparisons, although 324 genes demonstrated outlier (i.e. elevated) dN/dS ratios. Gene ontology analyses of these outliers revealed significant enrichment of genes associated with reproduction including meiosis and gametogenesis, following predictions of divergent selection between sexual and apomictic reproduction, although no significant signal of genome‐wide mutation accumulation could be identified. The results suggest that gene function should be considered in order to understand effects of mutation accumulation in asexual lineages.